Strategi manajemen perbankan syariah dalam menghadapi manajemen risiko pada era digital - Farichah, Miftahul (Maliki Interdisciplinary Journal, 2024)
In the ever evolving digital era, Islamic banks face new challenges in providing safe, advance and reliable banking services. This research aims to determine the strategy of Islamic banking in identifying risk management faced by banking in the digital era. This study uses a qualitative method with a descriptive approach. The data collection technique in this study is to use secondary data sources through literature reviews and previous research sources. The results of the study show that Islamic banking has several strengths, such as compliance with Islamic principles, customer loyalty, and opportunities to innovate in digital products. However, weaknesses in technological infrastructure and digital understanding, as well as resistance to change, are obstacles that need to be overcome. Therefore, Islamic banking needs to develop a risk management strategy that is integrated with modern technology, strengthening digital infrastructure. In addition, collaboration with fintech and strengthening human resource capabilities in technology will be key to facing challenges in the digital era.